Conservation Management Plan as a cultural heritage protection methodology - Trzaska, Rafał (Journal of Education, Health and Sport, 2017)
In this paper author describe how important is conservation management plan. Conservation management plan do not have support in law articles, therefore authors which create documents (documents in meaning conservation management plans) have not defined what they should put in to it. In this case, wrong written conservation management plan often is harmful than helpful for conservation management process.